Profil kadar metabolit sekunder: Steroid, alkaloid, dan tanin ekstrak daun bintangur (Calophyllum soulattri) - Kurniawan, Hadi; Nurbaeti, Siti Nani; IH, Hariyanto; Nugraha, Fajar; Fajriaty, Inarah (Universitas Mataram, 2024)
Bintangur leaf is one of the potential plants to be developed into a standardized herbal medicine which has many benefits such as antioxidant, anti-inflammatory and antibacterial. The aim of this study is to determine the steroid, tannin, and alkaloids of bintangur leaf extract. Preparation of bintangur leaves was conducted by soxhletation extraction technique with 96% ethanol as solvent. Determination of tannin tannic acid equivalent, and alkaloid quinine equivalent was analyzed by UV-Vis spectrophotometry method. While the analysis of steroid content Î²-sitosterol equivalent using a TLC Scanner. The results of the analysis showed that steroid content was 11061,49 ÂµgBSE/g, alkaloid was 307,16 ÂµgQE/g, and tannin was 6,586 %w/w TAE.